2016
DOI: 10.3928/01477447-20160623-14
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Resurfacing Versus Circumferential Denervation of the Patella in Total Knee Arthroplasty

Abstract: This study compared the rates of anterior knee pain and functional outcomes between resurfaced patellas and non-resurfaced patellas with a circumpatellar denervation. One hundred ten patients who underwent patellar resurfacing or a circumpatellar denervation were evaluated for knee pain and functional outcomes at a minimum of 2 years after total knee arthroplasty. There were no significant differences between the 2 groups regarding Knee Society Scores, anterior knee pain scores, or visual analog scale scores. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, according to the results of a recent study 17 , the efficacy of patellar resurfacing is imprecise. A study comparing patellar resurfacing and PD showed that there is no significant difference in the incidence of AKP with a 2-year FU 18 . As patellar resurfacing could result in several complications, such as fracture, loosening, and dislocation 19,20 , many surgeons prefer to not perform patellar resurfacing in TKA.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the results of a recent study 17 , the efficacy of patellar resurfacing is imprecise. A study comparing patellar resurfacing and PD showed that there is no significant difference in the incidence of AKP with a 2-year FU 18 . As patellar resurfacing could result in several complications, such as fracture, loosening, and dislocation 19,20 , many surgeons prefer to not perform patellar resurfacing in TKA.…”
Section: Discussionmentioning
confidence: 99%
“…VAS) before TKA, with non significant statistical difference between them. After 3 months of the operation, both groups were showing a slight decrease in VAS compared with that before TKA, with a non-significant statistical difference between them.This is due to the fact that in early period after TKA, the wound healing is notcomplete, leading to the slight VAS changes andthe non-significant difference between both study groups.It is worthwhile here to emphasize on wound healing problems which should be avoided during this period with the special and aggressive care, as the minimal incision infection can turn into a major complication (12). After 6 months of TKA, significant statistical difference (P< 0.05) was seen, and group (1) patients were more satisfied with progressive pain decrease.…”
Section: Figure (2): Total Knee Arthroplasty With Patellar Denervationmentioning
confidence: 97%
“…Several studies have shown equivalent clinical results with or without circumpatellar electrocautery. 132 135 In the most recent of these studies, Goicoechea et al found no significant difference in anterior knee pain or knee function scores in primary TKA with patellar resurfacing compared to patellar replacement without denervation. 135 Therefore, based on current results, patellar denervation cannot be recommended when patellar resurfacing is performed in TKA.…”
Section: Patellar Non-resurfacing Managementmentioning
confidence: 99%